The Politics of a Lover’s Complaints: Loss of Power as a Metaphor in Ghalib’s Urdu Verse - Dr. Muhammad Asif Khan (Journal of Research in Humanities, 2019)
In the nineteenth century India, the older indigenous culture which had achieved its zenith during the times of the great Mughal Empire gradually declined after the defeat of the last Mughal king in the 1857 rebellion against the British. Ghalib was not only an eyewitness to a great political change but he was also a victim of it. The present study is an effort to read Ghalib’s Urdu love poetry as a commentary on the discursive political situation in the Delhi of his times especially in the aftermath of the 1857 defeat. Ghalib has artistically used the canons of classical Urdu love poetry to reflect the ideological conflicts of his turbulent times. Seen from the New Historicist point of view, the lover’s complaints in Ghalib can be interpreted as the political statements issued by the deposed Mughal king. Ghalib’s dealings with his beloved may be read as negotiations between the commanding British rulers and the subdued Indian nobleman. Ghalib’s love poetry also gives useful insight into the reshaping of the individual identity under the impact of the experience of loss. Sometimes, we find Ghalib circulating subversive ideas. Ghalib’s times, especially the post 1857 years, were not suitable for the expression of subversive political ideas. Ghalib’s poetry shows that he was painfully aware of the precarious position not only of his native culture but also of his own individual position as the dignified member of a quickly vanishing culture. Ghalib’s poetry is an endeavour to give voice to the conflicted ideology of his time when survival as a virtue had become more relevant than the direct expression of political truths.